ANALISA TATA KELOLA TIEKNOLOGI INFORMASI UNTUK MENINGKATKAN DESTINASI PARIWISATA DI LOMBOK (STUDI KASUS DI DINAS PARIWISATA PROV. NTB) MENGGUNAKAN FRAMEWORK COBIT 5 - Septiana Rohman; Nadiyasari Agitha; Royana Afwani (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2020)
IT governance in a company to achieve the company’s vision, mission, goals, and objectives. There are problems in IT management both media and website in the Tourism Destination Development Sector, therefore this study determines the Capability level of IT governance in the Tourism Destination Development Sector using the COBIT 5 framework. The framework focuses on the APO01 sub-domain (Manage the IT management framework) Manage IT management frameworks, and APO04 (Manage innovation) Develop technological innovation. The results of the Capability level at APO01 for the current conditions are at levels 2 and 3, while the results of the Capability level at APO07, for now, are at level 2. While the Capability level results at APO01 and APO07 for the expected conditions are at levels 4 and 5 To increase the value of the Capability level got, recommendations for improvement are taken into consideration in the Development of Tourism Destinations in managing information technology.Then the recommendations given to increase the Capability level, form an action plan that is equipped with an implementation schedule and an estimated time that can be run